Azygos Vein Stenosis in Frontotemporal Dementia Sagging Brain Syndrome - Schievink, Wouter I.; Maya, Marcel M.; Saouaf, Rola; Lipshutz, H. Gabriel; Taché, Rachelle B.; Scoffings, Daniel; Schmahmann, Jeremy D. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: Symptoms indistinguishable from behavioral-variant frontotemporal dementia (bvFTD) can develop in patients with spontaneous intracranial hypotension associated with severe brain sagging. An underlying spinal CSF leak can be identified in only a minority of these patients and the success rate of nondirected treatments, such as epidural blood patching and dural reduction surgery, is low. The disability associated with bvFTD sagging brain syndrome is high and, because of the importance of the venous system in the pathophysiology of CSF leaks in general, we have investigated the systemic venous circulation in those patients with recalcitrant symptoms.MATERIALS AND METHODS: We reviewed the medical records and imaging studies of 21 consecutive patients with bvFTD sagging brain syndrome in whom no spinal CSF leak could be found and who underwent imaging of the systemic venous circulation (MR- or CT-venography). An SIH Disability Assessment Score (SIHDAS) questionnaire was completed to assess the severity of the symptoms.RESULTS: The mean age of the 3 women and 18 men was 50 years (range, 26–68 years). Seven patients were found to have venous stenosis. Endovascular stent placement of moderate to high-grade azygos vein stenosis in 3 patients resulted in prompt and remarkable improvement of symptoms in 2 patients (SIHDAS: very severe disability to no or mild disability) and mild improvement in 1 patient (SIHDAS: very severe disability to severe disability). Treatment of internal jugular vein and inferior vena cava stenosis in 2 patients each did not result in any improvement of symptoms. Endovascular (5 patients) or surgical (2 patients) interruption of multiple epidural spinal venous pathways did not result in any clinical improvement.CONCLUSIONS: The azygos vein is the main conduit between the spinal CSF space and the systemic venous circulation and this study demonstrates that isolated azygos vein stenosis may be a cause of spinal CSF loss and sagging brain syndrome. In this study, the yield of finding a clinically important treatable venous lesion among patients with recalcitrant bvFTD sagging brain syndrome was relatively low (15%). However, high quality and safe noninvasive imaging of the systemic venous system is available, eg, MR-venography, and should be considered for those patients who have exhausted treatments for this devastating condition, focusing on the azygos system.APantero-posteriorbvFTDbehavioral-variant frontotemporal dementiaDSMdigital subtraction myelographyIJVinternal jugular veinIVCinferior vena cavaSIHspontaneous intracranial hypotensionSIHDASSIH Disability Assessment Score